O papel de receptores de imunidade inata βGR, MR, TLR2 e TLR4 no reconhecimento da Candida albicans por monócitos humanos estimulados com polissacarídeos extraídos do cogumelo Agaricus brasiliensis - Martins, Priscila Raquel [UNESP] (2009)
Agaricus brasiliensis is a mushroom whose medicinal properties include antitumoral and immunomodulatory activities. The main bioactive substances of this mushroom are polysaccharides obtained from the fruiting bodies, being their immunomodulatory activities attributed mainly to -glucans. In this paper we aimed to study the role of a polysaccharide–rich fraction (ATF) of this mushroom on innate immunity receptors expression such as -glucan and mannose receptors (GR and MR), toll-like receptors (TLRs:TLR2 and TLR4) , phagocytosis of Candida albicans, cytokine production (TNF-, IL-1, IL-12 and IL-10) and H2O2 and NO release by human monocytes. ATF significantly increased Candida adherence/ phagocytosis by modulating TLR2 and TLR4 expression, since this polysaccharide had no effect on GR and MR as well as on H2O2 and NO production. Moreover, this polysaccharide increased IL-1 and TNF- production, being this effect also related to its capacity to increase TLR2 and TLR4 respectively. IL-10 levels were also increased. However an association between this effect and toll like receptors expression was not detected. In summary, our results provide evidence about the role of this extract on host resistance against some infectious agents through modulation of some phagocytic cells activities, including those of human monocytes